PEMBANGUNAN PARIWISATA BERKELANJUTAN DI DESA ADAT OSING KABUPATEN BANYUWANGI - Eka Maylinda; Sudarmono Sudarmono (Jurnal Environmental Science, 2021)
Since its establishment as a traditional tourism village in 1995, Kemiren Village has transformed in its development process. This article aims to 1). describe sustainable tourism development in the Osing Cultural Village, Banyuwangi; 2). analyze the constraints for sustainable tourism development in the Osing Cultural Village, Banyuwangi, and 3). scrutinize the supporting factors for sustainable tourism development in the Osing Traditional Village, Banyuwangi Regency. By using a qualitative design, this study relies on the method of collecting data through in-depth interviews to obtain data from key informants. This research found that the tourism sector contributes significantly to the creation of job opportunities for the villagers. Even so, this economic development does not necessarily diminish the roots of culture and customs that have persisted for a long time. However, the level of community awareness of environmental sustainability still needs to be improved. In carrying out its function, the government continues to make maximum efforts to issue regulations that can ensure the success of sustainable tourism development in Kemiren Village.